Land Potential Analysis for Health Service Facilities (Puskesmas) in the Pinangsia Village, DKI Jakarta Province - Prama Ardha Aryaguna, S.Si., M.Sc.; Horas Maulite Andrey Gromiko; Dayu Ariesta Kirana (Universitas Lambung Mangkurat, 2023)
Provision of Health Facilities is one of the government's mandates in ensuring public health in accordance with the 1945 Constitution article 34 paragraph 3